The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4236/ijoc.2014.43019
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient, One Pot Synthesis and Oxidation of Hantsch 1,4-Dihydropyridines Mediated by Iodobenzene Diacetate (III) Using Conventional Heating, Ultrasonic and Microwave Irradiation

Abstract: A mild, general, convenient, and efficient one-pot synthesis of 4-arylpyridines (4) is described using conventional heating, ultrasound and microwave irradiation. Aryl aldehydes (2) were efficiently condensed with ethylacetoacetate (1) and ammonium acetate in acetonitrile to give dihydropyridine intermediates (4). The latter underwent a smooth Iodobenzene Diacetate (III) mediated aromatization reaction in the same pot to afford 4-arylpyridines (4) in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Under various conditions, the Hantzsch condensation reaction of pyrazole-4-carboxaldehyde 2 with βketoester 64 and ammonium acetate or ammonia afforded the corresponding dihydropyridines 182. 131,[176][177][178][179][180][181][182][183] Similarly, N-aryl-1,4-dihydropyridines 183 were prepared by heating the 1,3-diphenyl-1H-pyrazole-4carboxaldehyde 2, ethyl acetoacetate/acetylacetone 64 and substituted anilines 184 165 Also, it was reported that the cyclocondensation of pyrazole-carboxaldehyde 2 with urea 120 or thiourea 184 120,185 and ethyl cyanoacetate 64 in the presence of sodium ethoxide 120 or potassium carbonate 185 gave the corresponding 2-oxo(thioxo)pyrimidine derivatives 185 (Scheme 79).…”
Section: Scheme 75 Synthesis Of Pyridine-3-carbonitriles 178mentioning
confidence: 99%
“…Under various conditions, the Hantzsch condensation reaction of pyrazole-4-carboxaldehyde 2 with βketoester 64 and ammonium acetate or ammonia afforded the corresponding dihydropyridines 182. 131,[176][177][178][179][180][181][182][183] Similarly, N-aryl-1,4-dihydropyridines 183 were prepared by heating the 1,3-diphenyl-1H-pyrazole-4carboxaldehyde 2, ethyl acetoacetate/acetylacetone 64 and substituted anilines 184 165 Also, it was reported that the cyclocondensation of pyrazole-carboxaldehyde 2 with urea 120 or thiourea 184 120,185 and ethyl cyanoacetate 64 in the presence of sodium ethoxide 120 or potassium carbonate 185 gave the corresponding 2-oxo(thioxo)pyrimidine derivatives 185 (Scheme 79).…”
Section: Scheme 75 Synthesis Of Pyridine-3-carbonitriles 178mentioning
confidence: 99%
“…They have also been reported to possess antidiabetic [18], anti-inflammatory [19], antimicrobial, calcium channel blocker [20], antitumor [21], and antitubercular [22] activities, etc. Various conventional and green protocols have been reported for the synthesis of DHPs using different catalysts such as AlCl3⋅6H2O [23], CeCl3⋅7H2O [24], Ceric ammonium nitrate [25], Fermenting baker's yeast [26], HClO4⋅SiO2 [27], HY-zeolite [28], Ionic liquids [29], K10-montmorillonite clay [30], Molecular iodine [31], magnetite/chitosan [32], Ni nanoparticles [33], Organocatalysts [34], p-TSA [35], SiO2 [36], triethylamine [37], TMSCl [38], ZnO [39], Fe-CuZSM-5 [40], microwave irradiation, and Ultrasound [41], etc. by the multi-component approach.…”
Section: Introductionmentioning
confidence: 99%